Membrane-Permeable 5-Fluorodeoxyuridine Triphosphate Derivatives Inhibit the Proliferation of Plasmodium falciparum - Nikolova, Vella Georgieva; Linnemannstöns, Karen; Bendel, Marie-Elise; Machado, Marta; Ganter, Benedikt; Budimir, Patricia; Vogts, Michelle; Fischer, Celine; Ganter, Markus; Meier, Chris; Dobbelstein, Matthias (ACS infectious diseases, 2025)
Malaria tropica remains a major global health challenge, raising the need for new therapeutic strategies against Plasmodium falciparum. While nucleoside analogues are effective against viruses and cancer, their use against P. falciparum is limited by the lack of nucleoside kinases in this species. To overcome this, we generated and tested cell-permeable derivatives of 5-fluorodeoxyuridine triphosphate (cpFdUTP) for antiparasitic activity in infected human red blood cells. cpFdUTP rapidly and potently inhibited the proliferation of P. falciparum, arresting development at the trophozoite-to-schizont transition by stalling DNA replication, as observed in a P. falciparum nuclear cycle sensor line. Although cpFdUTP also impaired the growth of human cells, supplementation with thymidine or cell-permeable deoxythymidine triphosphate (cpdTTP) selectively rescued human cells while maintaining parasite inhibition. This identifies a potential therapeutic window for cpFdUTP in combination with thymidine, outlining a novel approach for malaria treatment.